Impact du changement climatique sur les températures journalières minimales et maximales et les précipitations de la région de Tanger (nord-ouest du Maroc) quantifié à partir d’une méthode de descente d’échelle statistique - Nabil Rifai; Abdellatif Khattabi; Laila Rhazi (VertigO)
A statistical downscaling model (ASD) was evaluated by simultaneously downscaling maximum temperature, minimum temperature, and precipitation in Tangier's region (North-Western Morocco). The data used for evaluation were large-scale atmospheric data encompassing daily NCEP reanalysis data and the daily mean climate model results for scenarios A2 and B2 of the HadCM3 model and scenario A2 of the MCCG3 model. Selected as climate variables for downscaling were measured daily maximum temperature, daily minimum temperature, and precipitation data (1961 - 2000) from the weather station of Tangier. The results show that the pattern of change and numerical values of the temperature can be simulated, with the coefficients of determination between observed and downscaled daily maximum temperature and daily minimum temperature that attain 90% and 81%, respectively. However for precipitation, the statistical relationship still relatively weak, this is illustrated by a coefficient of determination that not exceed 20%.During 2061 – 2100, A2 scenario expect an increase for the maximum air temperature and the minimum temperature that attain about 2,9 °C but precipitation would decrease by about 49%. In the same trend, B2 scenario simulate an increase for the maximum air temperature and the minimum temperature by about 1,8 °C and 1,6 °C respectively and precipitation would decrease by about 45%. Thus, the climate of the North-Western Morocco tends to aridity with more warmer and drier conditions.